2006
DOI: 10.1159/000095742
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation during Mental Maze Solving

Abstract: Background: So-called Porteus mazes are used to investigate prefrontal cortex (PFC) functioning in normal subjects and patients with different neuropsychiatric disorders. Here we present data confirming the involvement of the PFC for the first time by means of functional magnetic resonance imaging (fMRI). To minimize motor-related activation, mental mazes were used. Methods: Mazes as well as pseudo-mazes without any bifurcations were presented to 49 healthy participants during fMRI scans. Results: Both, mazes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
(35 reference statements)
2
16
0
3
Order By: Relevance
“…The only significant performance decrement exhibited by heroin addicts was on the measure of cognitive impulsivity. One neuroimaging (fMRI) study links performance on this task to activation of bilateral areas of the prefrontal cortex, subcortical and cortical motor areas (Kirsch et al, 2006). Two additional studies included tasks that largely recruit the orbitofrontal portion of the prefrontal cortex (OFC).…”
Section: Studies With Normalmentioning
confidence: 99%
“…The only significant performance decrement exhibited by heroin addicts was on the measure of cognitive impulsivity. One neuroimaging (fMRI) study links performance on this task to activation of bilateral areas of the prefrontal cortex, subcortical and cortical motor areas (Kirsch et al, 2006). Two additional studies included tasks that largely recruit the orbitofrontal portion of the prefrontal cortex (OFC).…”
Section: Studies With Normalmentioning
confidence: 99%
“…Maze tests have been used in research and clinical practice to enable the evaluation of different cognitive and motor processes (OTT et al, 2003;SOUZA;FRANÇA;CAMPOS, 2006;KIRSCH et al, 2006). The task of solving a maze involves attention and perception during the analysis of the visuospatial stimulus, executive function at the moment of planning, organization and motor action, as well as when deciding on the correct solution path, especially when encountering a fork in the path.…”
Section: Introductionmentioning
confidence: 99%
“…The task of solving a maze involves attention and perception during the analysis of the visuospatial stimulus, executive function at the moment of planning, organization and motor action, as well as when deciding on the correct solution path, especially when encountering a fork in the path. The response is planned based on decisions made, trial and error, and performance improves through various trials until it is stabilized and the learning process is understood; the information is then stored in memory (KIRSCH et al, 2006). Studies using functional magnetic resonance imaging (fMRI) have shown evidence of an activation pattern of numerous cerebral structures linked to different cognitive and motor processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os resultados desse estudo sugerem uma correlação positiva entre a impulsividade motora e a ativação de áreas do córtex pré-frontal ventrolateral durante inibições comportamentais bem sucedidas. Esse resultado corrobora a interpretação que importantes áreas do córtex pré-frontal estão envolvidas tanto na modulação de respostas inibitórias (Bari & Robbins, 2013) quanto nos processos de planejamento e autorregulação do comportamento em tarefas de resolução de labirintos visuoespaciais (Kirsch et al, 2006).…”
unclassified